Living with haemophilia - Jones Peter 1937 (Lancaster [Lancashire] ; |a Boston : b MTP Press, 1984)
Presents causes and treatments of bleeding disorders and how to live within the limits they impose regarding activities, education, employment, sex, and family planning.
Includes index.
Bibliography: p. 169.
Keywords: Hemophilia -- Hemophilia in children -- Hemophilia